Sleep habits, parasomnias and associated behaviors in school children with attention deficit hyperactivity disorder (ADHD) - (:unkn) unknown (My University, 2011)
Considerable clinical data support an association between sleep problems and attention deficit hyperactivity disorder (ADHD). We aimed to investigate the sleep habits, associated parasomnias and behavioral symptoms in primary school children with ADHD. Forty primary school children with a clinical diagnosis of ADHD and 40 age-sex-matched healthy community controls were recruited. The Children's Sleep Habits Questionnaire providing information regarding sleep habits and nighttime and daytime symptoms was used. About 22% of children with ADHD (versus 2.9% of the controls) needed their parents to accompany them while going to sleep (p: 0.008). Transitional objects were needed by 8.1% of ADHD children in contrast to 2.9% of controls. Nightmares, overactivity during sleep, habitual snoring, and bed-wetting were significantly higher in the ADHD group. ADHD children needed significantly more time to go to sleep on school days (p < 0.02). Children undergoing evaluation for ADHD should be routinely screened for sleep disturbances.
Keywords: Female; Humans; Surveys and Questionnaires; Adolescent; Male; Child; Case-Control Studies; Attention Deficit Disorder with Hyperactivity; Analysis of Variance; Sleep Wake Disorders; Behavioral Symptoms; Habits